Application of contemporary smart building architecture at the Parahyangan Citywalk Shopping Center in Kota Baru Parahyangan - Agung Prabowo Sulistiawan; Muhammad Aflah Fernanda; Andiyan Andiyan (Jurnal Teknika, 2021)
Under the development of an increasingly modern era, intelligent buildings and infrastructure need to be built and operated in line with the progress of the future city. The shopping center building is a building that became one of the hallmarks of the city. Therefore the application must be prominent in the surrounding building. The concept is the basis for taking the use of contemporary concepts. The scope of this research is on the design of Shopping Center buildings that follow modern architectural trends and the interaction of trends on public needs in the future. The purpose of this study is to design a shopping center facility that combines the concept of contemporary architecture with the idea of intelligent building as a supporting element so that the building can adapt to the times in the digitalization era of the industrial revolution 4.0. The method used in this research is descriptive qualitative by applying seven principles of contemporary architecture and the concept of intelligent building in designing supporting facilities. The result of this research is a design of a shopping center building in Kota Baru Parahyangan Bandung by applying a combination of contemporary architectural concepts and intelligent building concepts that pay attention to the orientation and aspects of the surrounding environment. The combination of this concept not only cares for its completeness but also accommodates a lifestyle so that this shopping center can attract visitors with its technological innovations and the visual appearance of elegant contemporary architecture. Sesuai perkembangan zaman yang semakin modern, bangunan pintar dan infrastruktur perlu dibangun dan dioperasikan seiring dengan kemajuan kota masa depan. Bangunan pusat perbelanjaan merupakan bangunan yang menjadi salah satu ciri dari kemajuan suatu kota. Sebuah kota dapat dikatakan memiliki kemajuan apabila memiliki sebuah fasilitas yang baik dan lengkap. Salah satu fasilitas yang harus dimiliki suatu daerah adalah sebuah pusat perbelanjaan. Ruang lingkup penelitian ini difokuskan pada perancangan bangunan pusat perbelanjaan yang mengikuti tren arsitektur kontemporer dan tren interaksi kebutuhan publik di masa depan. Tujuan penelitian ini adalah mendesain sebuah fasilitas pusat perbelanjaan yang memadukan konsep arsitektur kontemporer dengan konsep smart building sebagai unsur penunjangnya agar bangunan dapat menyesuaikan dengan perkembangan zaman di era digitalisasi revolusi industry 4.0. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan menerapkan tujuh prinsip arsitektur kontemporer dan konsep smart building dalam merancang fasilitas penunjang pada bangunan pusat perbelanjaan ini. Hasil penelitian ini adalah sebuah rancangan bangunan pusat perbelanjaan di Kota Baru Parahyangan Bandung dengan menerapkan perpaduan konsep arsitektur kontemporer dan konsep smart building yang memperhatikan orientasi dan aspek lingkungan sekitar. Perpaduan konsep ini tidak hanya memperhatikan kelengkapan fasilitasnya saja namun dapat menampung kegiatan gaya hidup penggunanya sehingga pusat perbelanjaan ini dapat menjadi daya tarik bagi para pengunjung dengan inovasi teknologinya dan tampilan visual arsitektur kontemporer yang elegan.